THE NATURAL POTENTIAL AS A PREMISE FOR THE DEVELOPMENT OF TOURISM IN SĂLAJ COUNTY, ROMANIA - RUSU, Raularian; DEZSI, Ștefan; DOLEAN, Bogdan Eugen; MAN, Titus; MOLDOVAN, Ciprian (Studia Universitatis Babeș-Bolyai Geographia, 2020)
The tourism resources integrate the totality of attractive elements within a territory. The natural attractions of Sălaj County have been approached in this paper by analysing the four categories that are long-established in the scientific literature: morphological, climatic, hydrological and biogeographical tourist attractions. The geographical location of Sălaj County provides a privileged situation and a relative geographical unity, marked by a complex and complementary natural environment derived from the presence of a varied morphology. The karst morphology includes caves (Cuciulat, Măgurici), gorges (Babei Gorges), karst springs (Barcău Springs), and other attractions. The alternation of hard rocks and softer rocks, more friable and less resistant to erosion, led to the emergence of interesting forms, the result of differential erosion, such as the Dragons’ Garden (Grădina Zmeilor), the Devil’s Rock (Stânca Dracului), ”The Old Man and the Old Woman” (”Moșu și Baba”). Mineral and thermal waters are used for curative purposes at Băile Boghiș, Băile Bizușa, Jibou and Șimleu Silvaniei. The biogeographical potential is represented mainly by the vegetation cover, which is very diverse, including both forests and valuable flowering plants. Sălaj County has a significant natural potential, which is yet to be capitalized from the perspective of tourism, because natural attractions in Sălaj County are still little known to tourists, even in Romania.